The Effect of Deafferentation on Cerebral Blood Flow Response to Acetazolamide - Yamauchi, Hiroshi; Okazawa, Hidehiko; Sugimoto, Kanji; Kishibe, Yoshihiko; Takahashi, Masaaki (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Decreased cerebral blood flow (CBF) response after acetazolamide administration may indicate increased cerebral blood volume (CBV) owing to reduced perfusion pressure from major cerebral artery steno-occlusive disease. However, decreased cerebral metabolic rate of oxygen (CMRO2) caused by neuronal damage or deafferentation may also decrease the CBF response to acetazolamide, which adds complexity to the assessment of autoregulatory vasodilatation. The purpose of this study was to investigate the relationship between CBF response to acetazolamide and CBV or CMRO2 in a pure form of deafferentation, crossed cerebellar diaschisis (CCD).METHODS: We used positron emission tomography to study 17 patients with unilateral supratentorial infarct and contralateral cerebellar hypoperfusion. The CBF response to acetazolamide was assessed by measuring baseline CBF and CBF 10 minutes after an intravenous injection of acetazolamide. Multivariate analysis was used to test the independent predictive value of the CBV and CMRO2 at baseline with respect to the change of CBF during acetazolamide administration.RESULTS: Multivariate analysis revealed that in CCD CBV was significantly and independently associated with the percent change of CBF during acetazolamide administration (P < .0001), whereas CMRO2 was not.CONCLUSION: In deafferentation, changes in CBV may account for variations in CBF response to acetazolamide and decreased CMRO2 may not affect CBF response to acetazolamide expressed as the percent change.